2001
DOI: 10.1021/ie000951l
|View full text |Cite
|
Sign up to set email alerts
|

Fixed-Bed Hydrogenation at Supercritical Conditions To Form Fatty Alcohols:  The Dramatic Effects Caused by Phase Transitions in the Reactor

Abstract: Natural fatty alcohols are one of the major oleochemicals and can be produced by catalytic hydrogenation of fatty acid methyl esters. In the commercial multiphase process, the hydrogen availability to the solid catalyst limits the reaction rate. By adding propane to the reaction mixture, we can utilize the unique properties of supercritical fluids, properties between those of gases and liquids. Using propane, a substantially homogeneous supercritical phase is created, whereby hydrogen has complete access to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 17 publications
2
36
3
Order By: Relevance
“…A comparison between the novel hydrogenation technology under supercritical conditions in this work and the conventional process of liquid-phase hydrogenolysis of fatty ester shows that the ratio of hydrogen to FAME in reaction system is reduced by 90-98%, and the temperature and pressure of reaction is decreased significantly also in this work. It can be concluded from the reaction conditions that the pressure of this novel process here is lower by about 5.0 MPa than that for the process reported by other researcher [4] .…”
Section: Resultscontrasting
confidence: 62%
See 1 more Smart Citation
“…A comparison between the novel hydrogenation technology under supercritical conditions in this work and the conventional process of liquid-phase hydrogenolysis of fatty ester shows that the ratio of hydrogen to FAME in reaction system is reduced by 90-98%, and the temperature and pressure of reaction is decreased significantly also in this work. It can be concluded from the reaction conditions that the pressure of this novel process here is lower by about 5.0 MPa than that for the process reported by other researcher [4] .…”
Section: Resultscontrasting
confidence: 62%
“…The study on hydrogenation of FAME to FA using propane and carbon dioxide as solvents under supercritical conditions has been reported previously. But the reaction is carried out above 15.0 MPa [2][3][4][5] , and such high operation pressure will seriously increase the capital and operating costs. It is thus clear that a low-pressure hydrogenation process for FAME conversion to FA under supercritical conditions can lead to reduction in the capital and operating costs of the process while the advantages of supercritical reactions are maintained, which can also lead to great social and economic benefits.…”
Section: Introductionmentioning
confidence: 99%
“…In our experiments, noncondensing conditions were monitored by watching the increase in pressure drop across the reactor in the same way as reported by Van den Hark and Härröd (2001). We observed that one-phase equilibrium conditions are theoretically met but the system requires a finite or longer contact time to reach fluid uniformity.…”
Section: Achieving One-phase Fluid Mixturementioning
confidence: 87%
“…The use of supercritical fluids in deoxygenation can allow the operating temperature and process duration to be decreased. Moreover, compounds such as alcohols and hydrocarbons in the supercritical state can serve as hydrogen atom donors . Thus, no molecular hydrogen is required for the process.…”
Section: Introductionmentioning
confidence: 99%